2014
DOI: 10.1002/sia.5473
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of nanoindentation experiments of single‐layer and double‐layer thin films using finite element method

Abstract: In this work, we focused on investigations of mechanical properties of SiNx and diamond‐like carbon thin films deposited by plasma‐enhanced chemical vapour deposition method for application in optical devices or solar cells. Mechanical properties of thin films deposited on clean and oxidized silicon substrates were determined by nanoindentation. The main difficulty with the characterization of thin films using nanoindentation method is related to the influence of the substrate on the measured properties of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, the main limitations of this technique are the indentation depth, complex distribution of the indentation induced stresses and relatively costly experimental setup. Generally, FEM (finite element method) based simulations and analytical models are used to study the experimental load versus indentation depth curve and corresponding elastic-plastic stress distribution in thin films [30][31][32][33][34][35][36][37][38]. In addition to static tests, non-destructive dynamic tests based on the resonance frequency have also be implemented to evaluate the elastic behavior and residual stress in the thin films [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main limitations of this technique are the indentation depth, complex distribution of the indentation induced stresses and relatively costly experimental setup. Generally, FEM (finite element method) based simulations and analytical models are used to study the experimental load versus indentation depth curve and corresponding elastic-plastic stress distribution in thin films [30][31][32][33][34][35][36][37][38]. In addition to static tests, non-destructive dynamic tests based on the resonance frequency have also be implemented to evaluate the elastic behavior and residual stress in the thin films [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the inability to define a correct and applicable area function for the indentation tip at very shallow penetration depths [25]. In our case, experiments have shown that the tip area function is not a significant source of error for indentations of contact depths larger than about 80 nm [26]. Unfortunately, for this indentation depth, the influence of the substrate on the measurement results is too big.…”
Section: Mechanical Characterizationmentioning
confidence: 83%
“…However, the distribution of these fields is difficult to determine experimentally since several phenomena are involved in the scratch test, such as elastoplasticity, fracture, and wear caused by the excessive deformations on the sample [22,23]. Theoretical models can predict the stresses generated by scratching, where the complex deformation at the indenter-surface contact has been reproduced using numerical simulation with high correspondence to the actual phenomena [23][24][25][26][27][28][29][30][31][32][33][34][35]. The finite element (FE) method is a suitable tool for understanding the behavior of the stress-strain field [24].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the scratch process of thin films using FE has been used to understand the different types of damage on film-substrate systems [25][26][27]. For instance, the plastic deformation zone under the indenter tip has been assessed through the Von Mises criterion, even when the studied film presented a brittle behavior [28,29]. However, the differences between the brittle and ductile behaviors of the film-substrate system require a theory that considers such mechanical variations during the analysis of scratch tests.…”
Section: Introductionmentioning
confidence: 99%